PENDAMPINGAN PELATIHAN PEMAHAMAN PENDIDIKAN KARAKTER PADA GURU DI RUMAH BELAJAR: PENDAMPINGAN PELATIHAN PEMAHAMAN PENDIDIKAN KARAKTER PADA GURU DI RUMAH BELAJAR - Imas Kurniasih (LPPM STAI Darul Falah, 2023)
Character education is necessary not only at school, but also at home and in the social environment. Even today, the participants in character creation are not only for young learners and teenagers, but also adults. This training is important to be held to increase teacher insight regarding the implementation of character education for students. Apart from that, as an alternative to carry out integrated character education, namely combining and optimizing informal educational activities at home learning with formal education. Character education training for home learning teachers is carried out using the lecture and question and answer method. training participants can understand the importance of character education for students at home learning. Furthermore, the trainees will create various methods in the teaching process.